Technology-enabled carbon emissions regulations for achieving net zero carbon built environment: a comprehensive framework - Jong Han Yoon; Syeda Roushan Arshid (Carbon Management)
Enacting and implementing effective regulations for carbon emissions in the built environment is imperative in order to reduce emissions and thus achieve a net-zero built environment. While various technologies such as BIM, IoT, RFID, and Blockchain hold the potential to enable the successful enactment and implementation of emissions regulations, integrating their capabilities with regulatory processes has presented challenges. To bridge this gap, we conducted a systematic literature review focusing on carbon emissions regulations and emissions management technologies. The review uncovered two key aspects: firstly, the essential requirements for successfully enacting and implementing carbon emission regulations in the built environment, and secondly, the potential of technologies like BIM, IoT, RFID, and Blockchain to facilitate and support the identified prerequisites for successful regulation enactment and implementation. By integrating the findings from these two bodies of literature, we have developed a comprehensive framework for technology-enabled carbon emissions regulations. This framework offers valuable insights for policymakers and regulators, providing guidance on leveraging various technologies to effectively enact and implement carbon emissions regulations. Furthermore, it establishes a sturdy theoretical foundation for future empirical research on technology-enabled carbon emissions regulations by elucidating the intricate interplay between the prerequisites for successful regulation enactment and implementation and the application of diverse technologies.